2011
DOI: 10.1016/j.pmrj.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a New Application for Smartphones (DrGoniometer) for Elbow Angle Measurement

Abstract: Joint goniometry is a common mode of clinical assessment used in many disciplines, in particular rehabilitation [1][2][3]. One way to perform joint goniometry is through the use of computer-aided joint measurements from digital photographs [4][5][6][7][8]. This method entails a complex procedure to obtain the range of motion (ROM) value, which consists of the picture being manipulated upon by dedicated software once it has been downloaded from the camera to a computer.Recently, a new iPhone (Apple Inc, Cuperti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…al were investigating the iOS photogoniometer "DrGoniometer" in 2011 and 2013. In the former, the app was compared to a standard mechanical goniometer and judged reliable [11]. In the latter, the authors assessed in the same methodical setting angles in a knee joint, drawing the same conclusions [12].…”
Section: Discussionmentioning
confidence: 99%
“…al were investigating the iOS photogoniometer "DrGoniometer" in 2011 and 2013. In the former, the app was compared to a standard mechanical goniometer and judged reliable [11]. In the latter, the authors assessed in the same methodical setting angles in a knee joint, drawing the same conclusions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Good to excellent reliability has also been found for the measurement of the range of motion of other joints with the use of smartphone applications [10][11][12][13][14][15][16]. While studies have demonstrated that smartphone applications are reliable for use in research and clinical practice [3,6,[9][10][11][12][13][14][15][16], there is a wide diversity of goniometric applications to be tested. According to Milani et al [1], further studies are needed for the validation of these applications for different joints and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Ten orthopedic studies evaluated smartphone apps designed to measure joint angles and range of movement, either in real-time on live patients or from photographs or radiographic images of joints; these studies compared these novel methods with other well-established ''gold-standard'' techniques (see Table I). [20][21][22][23][24][25][26][27][28][29] Spinal, 24-26 shoulder, 27 elbow, 28 knee, [20][21][22][23] and metatarsophalangeal 29 joint angles were measured by apps using either the in-built smartphone accelerometer or a virtual in-app goniometer.…”
Section: Resultsmentioning
confidence: 99%